Projekt nosné železobetonové konstrukce - Klodner, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Diplomová práce řeší obecnou problematiku podlahových betonových desek, technologii, provádění, modely podloží, výpočet vnitřních sil a návrhové přístupy. Na základě těchto údajů pak sleduje chování podlahových desek dle různých parametrů. Součástí je také návrh konkrétní podlahové desky ve třech variantách. Drátkobetonové, železobetonové a předpjaté, včetně ekonomického srovnání. Byl rozpracován i návrh kalichové patky a železobetonového sloupu nosného systému haly, namísto původní klasické patky s ocelovým sloupem.

This thesis is focusing on general issues of floor concrete slabs, technology, implementation, subsoil models, calculation of internal forces and design approaches. Based on these data the thesis monitors the behaviour of floor slabs according to the various parameters. It also includes three versions of design of the real floor slab, made of steel fibre reinforced concrete, reinforced concrete and prestressed concrete. Economic comparison is also included. In addition it developes a design of the chalice base and reinforced concrete column of the supporting hall system, instead of the original usual base with steel column.
Design of Load Bearing Concrete Structure
Keywords: podlahová deska; model podloží; drátkobeton; železobeton; předpjatý beton; Soilin; analytický výpočet vnitřních sil; ČSN EN 1992-1-1; TR No. 34; Rilem Technical Committe; mezní stav únosnosti; mezní stav použitelnosti; diferenciální sedání; kalichová patka; interakční diagram; parametrické studie; floor slab; subsoil model; steel fibre reinforced concrete; reinforced concrete; prestressed concrete; Soilin; analytical calculation of internal forces; ČSN EN 1992-1-1; TR No. 34; Rilem Technical Committe; ultimate limit state; serviceability limit state; differential settlement; chalice base; interaction diagram; parametric study